Makna Akuntabilitas Lingkungan dalam Perspektif Pelaku Usaha Pariwisata Berbasis Ekowisata: Studi Kualitatif di Bali - Nyoman Suadnyana Pasek; Rindhi Maverissa (Lembaga Penelitian, Universitas Warmadewa, 2026)
This study aims to understand the meaning of environmental accountability from the perspective of ecotourism-based tourism operators in Bali. Environmental accountability has become a critical issue alongside the growing attention toward sustainable tourism development, which focuses not only on economic profit but also on environmental preservation and local community welfare. This study utilizes a qualitative approach with a phenomenological method to explore the experiences, understanding, and practices of environmental accountability implemented by ecotourism operators. Data were gathered through in-depth interviews, observation, and documentation involving several managers of ecotourism-based tourism businesses in Bali. The results indicate that environmental accountability is interpreted as a form of moral and social responsibility to preserve nature, culture, and the sustainability of tourist destinations. Environmental accountability practices are realized through waste management, reduction of plastic usage, natural resource conservation, and the involvement of local communities in business activities. Furthermore, operators perceive that the implementation of environmental accountability can enhance business image, tourist trust, and long-term economic sustainability. However, the implementation of environmental accountability still faces various obstacles, such as financial constraints, a lack of specific regulations, and low awareness among some business operators regarding the importance of environmental management. This study contributes to the development of environmental accounting literature, particularly within the ecotourism sector, and provides valuable insights for the government and business operators to foster sustainable tourism development practices in Bali.